ASSESSMENT OF FISHERY AND ECOLOGICAL INTEGRITY OF THE ANTHROPOGENICALLY STRESSED RIVER CHURNI, INDIA - DAS, M. K.; SAMANTA, S.; MITRA, K.; BANDYOPADHYAY, M. K.; BHOWMICK, S. (Journal of the Inland Fisheries Society of India, 2020)
The river Churni a major source of surface water provides food and income security to nearly 0.3 million riparian people. Anthropogenic activities over the years have resulted in frequent fish mortality and decline in fish population. The frequent discharge of sugar mill effluents in the river alter the dissolved oxygen to critical levels of 0.8 mg l-1. 54 fish species belonging to 24 families and 41 genera were recorded during the study. The relative abundance ofÂ  Cyprinids was maximum (0.7-16%) followed by Bagrids (1.5-3.6%). The dominant species across the sites were Puntius conchonius, Glossogobius giuris, Salmophasia bacaila and Amblypharyngodon mola. Carnivorous species (54%) were dominant in all sites followed by omnivores (26%) and herbivores (20%). The local fish assemblages were structured by environmental influences at multiple scales. The most important parameters determining variability of fish assemblages are DO, pH, CO2, NH3-N and hardness. Evaluation of fish health of L. rohita reared in cages in situ at the stressed site and at the non-stressed site of the river indicated significant alteration in blood chemistry and cellular structure of the fishes in the stressed site compared to the control. The Index of Biotic IntegrityÂ  revealed that 40 % of the sampled sites supported fish assemblages in acceptable condition. Appropriate management strategy has been suggested to restore the ecological integrity of the river.